2020
DOI: 10.3389/fneur.2020.00696
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep Disorders in Leucine-Rich Glioma-Inactivated Protein 1 and Contactin Protein-Like 2 Antibody-Associated Diseases

Abstract: Objective: Sleep disorders are common in voltage-gated potassium channel complex antibody (VGKC-Ab) diseases. The aim was to investigate the sleep disturbances and polysomnography (PSG) characteristics in patients with VGKC-Ab-associated diseases. Methods: Twenty-seven patients with leucine-rich glioma-inactivated protein 1 antibody (LGI1-Ab) encephalitis, seven patients with contactin protein-like 2 antibody (Caspr2-Ab)-associated diseases, and 14 healthy controls with at least one PSG or actigraphy recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
4
10
1
Order By: Relevance
“…FBDS has been thought to be an indicative seizure type that frequently preceded the onset of limbic encephalitis (30), and the incidence in our study was 33.3%, consistent with some important studies with an incidence of 34-47% (7,8,17); however, some studies reported a higher incidence of 66.7-100% (3,6,26,28,29). In addition to seizures, cognitive dysfunction, psychiatric disturbances, and sleep disorders were relatively common clinical manifestations, which occurred in 82.2, 66.7, and 54.5% of the patients, respectively, and these results were comparable to previous studies that reported incidences of 64.3-100% (3,6,8,11,17,25,26,28,29), 33.3-73% (3,6,8,17,(27)(28)(29), and 18.2-48% (3,8,11,25,26,28), respectively. In terms of auxiliary examinations, the rates of CSF pleocytosis and protein elevation were both 6.8%, and similar results were obtained in previous studies, with rates of 3.7-19.4% and 12.5-23.1%, respectively (3,11,27,29).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…FBDS has been thought to be an indicative seizure type that frequently preceded the onset of limbic encephalitis (30), and the incidence in our study was 33.3%, consistent with some important studies with an incidence of 34-47% (7,8,17); however, some studies reported a higher incidence of 66.7-100% (3,6,26,28,29). In addition to seizures, cognitive dysfunction, psychiatric disturbances, and sleep disorders were relatively common clinical manifestations, which occurred in 82.2, 66.7, and 54.5% of the patients, respectively, and these results were comparable to previous studies that reported incidences of 64.3-100% (3,6,8,11,17,25,26,28,29), 33.3-73% (3,6,8,17,(27)(28)(29), and 18.2-48% (3,8,11,25,26,28), respectively. In terms of auxiliary examinations, the rates of CSF pleocytosis and protein elevation were both 6.8%, and similar results were obtained in previous studies, with rates of 3.7-19.4% and 12.5-23.1%, respectively (3,11,27,29).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the frequency of OB and the rate of increased intrathecal IgG synthesis rate were both higher (30.0 and 17.5%, respectively), suggesting that they may be more sensitive than routine CSF examinations. The incidence of hyponatremia in the present study was also within the scope of previous studies (66.7 vs. 39-80%, respectively) (8,11,17,25,26,28,29); hyponatremia is often caused by inappropriate secretion of the antidiuretic hormone, which may be related to the expression of LGI1 in the hypothalamus and the kidney (31). Additionally, we found that 90.9% of the patients had typical abnormalities reflected in FDG-PET imaging, and 66.7% of the patients had MRI abnormalities, suggesting that the sensitivity of FDG-PET was much higher than that of structural MRI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to the control group, patients during active stage had severe loss of spindles, SWS and REM sleep, suggesting that the evolution of sequential sleep stages was disturbed and reaching deeper stages became more challenging. 3,12,13 We previously reported that there are abundant nocturnal episodic events during active phase of anti-LGI1 encephalitis, thus it is plausible to attribute the disorganized sleep structure to sleep interruption by these motor events. However, as described in this study, patients without motor events still encounter pronounced disruption of sleep structure during the active phase, suggesting that sleep instability in the anti-LGI1 group was independent of the presence of motor events.…”
Section: Discussionmentioning
confidence: 99%